Factor analysis of the effectiveness of assertive training techniques in reducing adolescent conformity behaviour - Nawawi, Erfan (Privietlab, 2025)
Adolescence is a critical developmental stage marked by physical, emotional, and social transitions, during which conformity to peer norms frequently emerges as a dominant behavioral pattern. While moderate conformity can foster social skills and prosocial behavior, excessive conformity often undermines adolescents’ self-concept and autonomy, leading to negative outcomes, such as bullying, substance use, and diminished academic achievement. This study examined the effectiveness of assertive training techniques in mitigating negative conformity behavior among adolescents. Employing a qualitative literature review, 145 articles published between 2019 and 2024 were initially identified through Google Scholar, with eight articles meeting the inclusion criteria for an in-depth analysis. The findings consistently reveal that assertive training techniques enhance adolescents’ ability to resist peer pressure, improve interpersonal communication, strengthen self-concept, and reduce dependency on social approval. The review highlights three critical factors shaping the success of assertive training interventions: (1) individual factors, such as self-confidence and interpersonal skills; (2) environmental factors, including supportive group dynamics in counselling settings; and (3) methodological factors, such as structured role-play, simulations, and staged training implementation. Complementary approaches, such as sociodrama, have also been found to be effective in addressing conformity by fostering awareness of group dynamics. Despite promising outcomes, the reviewed studies faced methodological limitations, including small sample sizes and limited control group comparisons. This study underscores the potential of assertive training as a preventive and corrective counselling strategy to address adolescent conformity, while also calling for future research employing more rigorous experimental designs to strengthen the empirical evidence and broaden practical applications in educational and counselling contexts.